LOWER SEMI-CONTINUITY OF THE SOLUTION SET TO A PARAMETRIC OPTIMAL CONTROL PROBLEM - Bùi Trọng Kiên; Nguyễn Thị Toàn; Mu Ming Wong; Jen Chih Yao (Tạp chí Khoa học Đại học Đà Lạt)
This paper studies the solution stability of a parametric optimal control problem with linear state equation, control constraints and convex cost functions. By reducing the problem to a parametric programming problem and a parametric variational inequality, we obtain the lower semi-continuity of the solution map to a parametric optimal control problem.